Commentary on “Social protection and the International Monetary Fund: promise versus performance” by Alexander Kentikelenis and Thomas Stubbs - James Pfeiffer (Globalization and Health)
Abstract Background The Covid pandemic and its aftermath have triggered new alarm and social unrest across the Global South over the deepening international debt crisis that now threatens to derail Universal Health Coverage (UHC), other Sustainable Development Goals (SDGs), future pandemic preparedness, and global warming mitigation. The recent Globalization and Health article by Alex Kentikelenis and Thomas Stubbs (May 2024), “Social protection and the International Monetary Fund: promise versus performance”, offers a meticulously quantified rendering of the social costs imposed by the crisis and takes aim at IMF solutions. They advocate for a rejection of IMF austerity programs and offer a valuable prescription for change through the International Labor Organization’s “Universal Social Protection” concept. Main body Similar to the Jubilee movement at the turn of the century, global civil society, humanitarian aid, and health organizations are mobilizing in a variety of global networks to call for debt cancellation and restructuring as well as an end to austerity. These include new debt law campaigns in London and New York to rein in private creditors, calls for new IMF issuance of “Special Drawing Rights”, demands for “Global Public Investment”, and promotion of Universal Social Protection. Conclusion The Universal Social Protection approach described by Kentikelenis and Stubbs provides a focal point for these demands to confront this latest and worst episode of sovereign debt crisis already undermining global health progress.